2016
DOI: 10.1039/c6dt01695b
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient dehydrogenation of formic acid in aqueous solution catalysed by an easily available water-soluble iridium(iii) dihydride

Abstract: The new water-soluble cis-mer-[IrH2Cl(mtppms)3] (mtppms = monosulfonated triphenylphosphine) was employed as a catalyst for selective decomposition of formic acid to H2 + CO2 in aqueous solution at T = 30-100 °C. The easily synthesized compound showed high catalytic activity (TOF up to 298 000 h(-1)) and could be reused several times with no loss of activity (total TON = 67 650). A sharp maximum in the reaction rate was observed at pH = 3.75; its coincidence with the pKa of formic acid shows that both H(+) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 56 publications
1
37
0
2
Order By: Relevance
“…We have found that a similar, but water-soluble iridium(I) complex, cisz-mer-[IrH 2 Cl(mtppms-Na) 3 ], 7 (Fig. 4) was outstandingly active in FA decomposition; in fact it showed the third highest activity (TOF = 298 000 h -1 ) among the known homogeneous catalysts of this reaction 26 . High chemical stability of 7 is exemplified by the high turnover number (TON = 674 000) obtained in the presence of a large excess of formic acid.…”
Section: Formiát/hidrogénkarbonát Alapú H 2 -Akkumulátorokmentioning
confidence: 93%
See 2 more Smart Citations
“…We have found that a similar, but water-soluble iridium(I) complex, cisz-mer-[IrH 2 Cl(mtppms-Na) 3 ], 7 (Fig. 4) was outstandingly active in FA decomposition; in fact it showed the third highest activity (TOF = 298 000 h -1 ) among the known homogeneous catalysts of this reaction 26 . High chemical stability of 7 is exemplified by the high turnover number (TON = 674 000) obtained in the presence of a large excess of formic acid.…”
Section: Formiát/hidrogénkarbonát Alapú H 2 -Akkumulátorokmentioning
confidence: 93%
“…Igen nagy katalitikus aktivitást észleltek ródium 17,18 , ruténium 19 és iridium 20 26 . 2 Cl(mtppms-Na) 3 ]-katalizálta bontásával -a hõmérséklet hatása.…”
Section: Hangyasav Katalitikus Dehidrogénezéseunclassified
See 1 more Smart Citation
“…Since our earlier studies, using both [RuCl 2 (mtppms) 2 ] and [IrH 2 Cl(mtppms) 3 ], showed excellent catalytic activities in hydrogenation and transfer hydrogenation of various unsaturated groups [17,18] and in decomposition of formic acid [12], we envisaged their applicability in transfer hydrogenation of the imine intermediates of glycan labeling by reductive amination (Figure 1). Figure 3A.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…To avoid the generation of the acutely toxic hydrogen cyanide, several substitutes were evaluated to replace the sodium cyanoborohydride as reductive agent. Figure 2) were made in house as described earlier in [12] and [13], respectively (Please note that the Ru(II)-complex has a dimeric structure in solid state as shown in Figure 2, however, for the sake of simplicity we refer to here as a monomer). Both complexes are highly water-soluble and can be synthesized easily from their halide precursors of IrCl 3 .3H 2 O [12] and RuCl 3 .3H 2 O [13], respectively, in reaction with monosulfonated triphenylphosphine (mtppms [13]).…”
Section: Introductionmentioning
confidence: 99%